Suggested activities to develop oral communication skills among grade three fast learners - Inot, Marciana S.; Baldo, Trinidad C. (1973)
The purpose of the study was to know the answers to the following questions: 1) why is there a need to develop the oral communication skills of the grade three fast learners? and 2) what specific activities may be given to grade three fast learners in order to develop their oral communication skills? Library research was the main method used in the study to obtain the needed information. The activities discussed in the study utilized the language aspects of listening and speaking but it puts great emphasis on the oral practice of the second language. Providing the fast learners with language experiences suited to their needs and interests will not only lead them to make effective self-expression but will also tap their creative potentials.
Thesis (Master of Arts in Teaching - Special Education : Giftedness)--University of the Philippines, Diliman.
Keywords: Oral communication -- Study and teaching (Elementary) -- Activity programs -- Philippines; Gifted children -- Education (Elementary) -- Philippines